Screening for Problematic Internet Use May Help Identify Impulse Control Disorders in Parkinson’s Disease - Márton Kovács; Attila Makkos; Dávid Pintér; Annamária Juhász; Gergely Darnai; Kázmér Karádi; József Janszky; Norbert Kovács (Behavioural Neurology)
Background. Impulse control disorders in Parkinson’s disease (PD) represent emerging problems with potentially devastating consequences. The standard screening methods for impulse control disorders are clinically imperfect. Although it is rarely reported, many patients utilize the Internet to fulfill their compulsive behaviors because of its easy accessibility. We designed a study to test the hypothesis that an active screening for excessive Internet use and Internet addiction might improve the sensitivity of identification of impulse control disorders. Methods. The standard screening method included the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease and the modified Minnesota Impulsive Disorders Interview. In the second round, the Problematic Internet Use Questionnaire was also assessed for detecting excessive Internet use. Results. While the standard approach identified 19 patients out of 106 (17.9%) with any type of impulse control disorders, screening for the problematic Internet use detected 29 patients with impulse control disorders (27.4%) having significantly better efficacy over the standard method (p=0.004, the McNemar test). Conclusions. Our study suggests that the screening for problematic Internet use by the Problematic Internet Use Questionnaire is an effective, feasible, and easy-to-use add-on method for identifying PD patients with impulse control disorders more efficiently and probably at earlier stages.